VISUAL EFEK UNTUK MEMBANGUN ELEMEN VISUAL DALAM MENCIPTAKAN REALITAS PADA FILM MISSION : IMPOSSIBLE - DEAD RECKONING PART ONE KARYA BRUCE GELLER - jaisyul - Usrah; Hery Sasongko (Institut Seni Indonesia Padang Panjang, 2025)
This study analyzes the role of visual effects (VFX) in constructing cinematic reality in the film Mission: Impossible - Dead Reckoning Part One (2023). The central problem is to understand how modern films utilize advanced digital technologies not just for spectacle, but as a fundamental tool for constructing believable and immersive worlds. The aim is to investigate how specific VFX techniques, particularly Computer Generated Imagery (CGI), green screen compositing, and digital matte painting, are used to create visual elements that convince the audience of the reality constructed by the film. The study uses qualitative visual analysis methods, guided by Stephen Prince’s theory of perceptual realism, to deconstruct key scenes from the film. The results show that the film skillfully integrates practical action with digital environments to achieve a high level of perceptual realism. Through careful observation of the laws of physics, lighting, and environmental textures, the film creates artificial worlds - from vast deserts and mountains to chaotic train crashes - that feel authentic and real, effectively immersing the audience in the tension and scale of the narrative.